Analisa Pengaruh Perubahan Beban Output Turbin Terhadap Efisiensi Boiler - Jatmiko Edi Siswanto (Universitas Batanghari Jambi, 2020)
In palm oil processing companies to become oil, the boiling process is carried out to make it easier for the loose fruit to come from the bunches, to stop the development of free fatty acids and will cause the tbs to soften so the oil extraction process becomes easier. The boiling process requires steam from steam. Steam is obtained by heating a vessel filled with water with fuel. Generally, boilers use liquid, gas and solid fuels. Steam functions as a boiling and electric generator, the company uses a boiler as a steam producer to support the production process. A boiler or steam boiler is a closed vessel used to produce steam through an energy conversion process. To find out the boiler efficiency, a calculation is carried out by taking the parameters needed for boiler operation, from the analysis the highest boiler efficiency results are 83.56% and the lowest is 75.25%, where the heating value with 13% fuel at 1000 Kw load is 83, 56%. And the calorific value with 10% fuel at a load of 750 Kw is smaller with a value of 75.25%.